RELIABILITAS METODE PENGUMPULAN DATA KONSUMSI MAKANAN TINGKAT RUMAHTANGGA DAN INDIVIDU (RELIABILITY DATA COLLECTION METHODS OF HOUSEHOLD AND INDIVIDUAL FOOD CONSUMPTION) - Sri Prihatini; Trintrin Tjukarni; Sri Mulyati (Persagi, 2011)
Abstract Background: One of constrains in the measurement of household food consumption through individual food consumption is difficult to meet all person for interviewing at the same time. Objective: To obtain an operational method of collecting food consumption data to estimate the level of energy intake of household from individual food consumption which aggregated to the household. Methods: Design of this study is cross-sectional. The research was conducted in Cianjur district and the city of Bandung, West Java province. Study sample are 360 households consisting 1489 individuals. The data collected is household and individual food consumption. The method used is 1 x 24 hours food-recalls. In analysis, households are grouped into 3 groups, which are: household that has complete member, household that represented by the age group of household members, and the household that has incomplete members. Kappa reliability test is performed to determine the proportion agreement of energy deficit household among analysis groups. Results: The average of adequacy level of energy collected from household consumption tended to be higher than those from individual consumption. Reliability test results of energy deficit household between household that has complete members and household level group has Kappa value of 0.15., while with household represented by the age group was 0.77 and with household that has incomplete members is 0.73. Conclusions: The reliability test of inter-analysis group showed that the highest kappa value of 0.77 is shown between groups household that has complete group and households that represented by the age group. This means that in order to estimate household consumption, the interview can be made to all household members or simply represented by age group in the household. Keywords: Reliability test, food consumption, household and individual level abstrak Latar Belakang: Salah satu kendala dalam penilaian konsumsi makanan rumah tangga melalui konsumsi individu adalah kesulitan menemui seluruh anggota rumah tangga pada waktu yang bersamaan. Tujuan: Mendapatkan suatu metode operasional pengumpulan data konsumsi makanan untuk mengestimasi tingkat konsumsi energi rumah tangga melalui konsumsi makanan individu, yang diagregatkan ke rumah tangga. Metode: Disain penelitian ini adalah Kross-seksional. Penelitian dilaksanakan di kabupaten Cianjur dan kota Bandung provinsi Jawa Barat. Sampel penelitian sebanyak 360 rumahtangga terdiri dari 1489 individu. Data yang dikumpulkan adalah data konsumsi makanan tingkat rumahtangga dan individu. Metode yang digunakan yaitu metode recall 1 x 24 jam. Dalam analisis, rumah tangga dikelompokkan menjadi 3 kelompok yaitu rumah tangga anggota rumah tangganya yang lengkap , rumah tangga yang diwakili kelompok umur dari anggota rumah tangganya dan rumah tangga tidak lengkap anggota rumah tangganya. Uji reliabilitas Kappa dilakukan untuk mengetahui kesepakatan proporsi rumah tangga defisit energi antar kelompok analisis. Hasil: Hasil penelitian menunjukkan bahwa rerata tingkat kecukupan energi yang dikumpulkan melalui konsumsi rumah tangga cenderung lebih tinggi dibandingkan dengan konsumsi energi dikumpulkan secara individu. Hasil uji reliabilitas rumah tangga defisit energi antara kelompok lengkap dengan kelompok tingkat rumah tangga mempunyai nilai Kappa sebesar 0,15. Kelompok lengkap dengan kelompok yang diwakili kelompok umur adalah 0,77 dan kelompok lengkap dengan kelompok tidak lengkap adalah 0,73. Kesimpulan: Uji reliabilitas antar kelompok analisis menunjukkan bahwa nilai Kappa tertinggi sebesar 0,77 ditunjukkan antara kelompok lengkap dan yang diwakili kelompok umur. Hal ini berarti bahwa untuk mengestimasi konsumsi rumah tangga dapat dilakukan wawancara kepada semua anggota rumahtangga atau cukup diwakili oleh kelompok umur yang ada di rumahtangga tersebut. [Penel Gizi Makan 2011, 34(2): 86-92] Kata kunci : Reliabilitas, Konsumsi makanan rumah tangga, konsumsi makanan individu